Prisma de formação caribenha: a produção social de uma consciência oposicional em C. L. R. James e Oliver C. Cox - Borda, Erik Wellington Barbosa (Universidade Federal de São Carlos, 2018)
This work consists in a contrast between the initial trajectories of two black authors of Trinidad and Tobago; C. L. R. James and Oliver C. Cox. The period of beginning is marked, in this research, from the birth of these authors until the publication of their magnum opi, 1938 for James and 1948 for Cox. The contrast was made having as its based a path opened by the Jamaican theorist Stuart Hall when he debated his trajectory, i.e., the idea of prism of Caribbean formation. It is argued, then, that the intellectual production of Afro-Caribbean authors may be read in the interstice between a flight from the dynamics of oppression inherent to a place of nonhumanity, the zone of Nonbeing, and the validation logics and horizons of possibilities reserved to black intellectuals in different national contexts. The magnum opi that marks this research’s chronological frame also denounces these dimensions through theoretical displacements that the authors have accomplished by a forced dialogue with Universalist Western intellectual traditions by which the authors they were formed.
Prism of caribbean formation: the social production of an oppositional consciousness in C. L. R. James and Oliver C. Cox
Keywords: Oliver C. Cox; C. L. R. James; Caribe; Intelectuais negros; Pensamento negro; Pensamento caribenho; Black intellectuals; Black thought; Caribbean; Caribbean thought; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS